Annualization of Fifth-Year Clinical Training in Dentistry: A Curricular Experience at the University of Costa Rica - Gutiérrez-Marín, Natalia (2026)
The aim of this study was to determine the academic impact of converting fifth-year clinical courses at the Faculty of Dentistry of the University of Costa Rica from a semester-based to an annual format by comparing approval, failure, and academic delay outcomes between the two curricular models. An observational retrospective study with longitudinal follow-up was conducted using institutional academic records of 670 students from entry years 2007-2020, with follow-up through December 2024. Student records were analyzed considering variables such as gender, age, admission note, clinic approval rates, and academic delay. Approval rates between curricular formats were compared using chi-square tests and multivariate logistic regression models (OR, 95% CI). Academic delay was analyzed descriptively by clinical discipline and curricular format.  Of the students included, 322 completed clinical courses under the semester-based system and 348 under the annual system. Statistically significant differences favoring the annual format were observed in Endodontics (79% vs. 64.3%; p<0.001) and Periodontics (91.4% vs. 83.5%; p=0.002), whereas Restorative Dentistry showed higher approval rates under the semester-based model (83.5% vs. 75.9%; p=0.014). No significant differences were found in Diagnosis, Oral Surgery and Exodontia, or Pediatric Dentistry and Orthodontics. Although a greater absolute number of students repeated courses under the semester-based format, failure in the annual format was associated with a longer mandatory academic delay (12 months vs. 6 months). The academic impact of annualization was heterogeneous across clinical disciplines, highlighting the importance of evaluating curricular reforms using objective indicators before consolidating permanent structural changes in dental clinical education.